Community Satisfaction with Zamboanga City Jail Services: Toward a Trust Rating Index - Aznar, Erizha Mae; Noceda, Ezrha Joy F; Villa, Jay Rim; Polingga-Villa, Laiza Jane L (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study assesses the levels of trust, respect, and satisfaction among clients of the Bureau of Jail Management and Penology (BJMP) in Zamboanga City Jail. As a vital institution within the Philippine correctional system, the BJMP plays a key role in upholding humane safekeeping and rehabilitation. Understanding client perceptions within this facility provides valuable insights into the effectiveness and quality of jail management and service delivery. Rooted in the constitutional principle that “public office is a public trust,” the research addresses a critical gap in empirical data on public perception of jail institutions. Using a descriptive research design, the study surveyed 300 respondents—persons deprived of liberty (PDL), their family members, and service providers—selected through purposive sampling. A validated questionnaire measured perceptions of trust, respect, and service satisfaction. Findings revealed a consistently high level of trust (overall trust index of 97%) and satisfaction across all groups, with mean scores above 5.70 on a six-point scale, indicating a "Very High" verbal interpretation. One-Way ANOVA results showed no significant differences among the groups’ responses (p = 0.42), suggesting equitable service perception across stakeholders. These outcomes demonstrate the effectiveness of BJMP’s rehabilitation programs and the strong institutional culture of transparency, professionalism, and mutual respect. The study concludes that high trust and satisfaction levels are key indicators of institutional performance and public confidence. It recommends institutionalizing a Trust Rating Index, enhancing communication strategies, and fostering research collaborations to further professionalize BJMP services and strengthen stakeholder engagement in correctional reform.